2020
DOI: 10.1038/s41598-020-76193-0
|View full text |Cite
|
Sign up to set email alerts
|

ZNF354C is a transcriptional repressor that inhibits endothelial angiogenic sprouting

Abstract: Zinc finger proteins (ZNF) are a large group of transcription factors with diverse functions. We recently discovered that endothelial cells harbour a specific mechanism to limit the action of ZNF354C, whose function in endothelial cells is unknown. Given that ZNF354C has so far only been studied in bone and tumour, its function was determined in endothelial cells. ZNF354C is expressed in vascular cells and localises to the nucleus and cytoplasm. Overexpression of ZNF354C in human endothelial cells results in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A previous study reported that ZNF354C is a key transcriptional factor in carcinogenesis and the development of esophageal squamous cell carcinoma (ESCC) by regulating targets genes [ 67 ]. Recently, a study revealed that ZNF354C is expressed in vascular cells, while ZNF354C overexpression inhibits the endothelial sprouting by binding to specific endothelial relevant target gene promoter [ 18 ]. In our study, we also proved that ZNF354C, as a transcriptional factor, could directly bind the promoter of TFPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that ZNF354C is a key transcriptional factor in carcinogenesis and the development of esophageal squamous cell carcinoma (ESCC) by regulating targets genes [ 67 ]. Recently, a study revealed that ZNF354C is expressed in vascular cells, while ZNF354C overexpression inhibits the endothelial sprouting by binding to specific endothelial relevant target gene promoter [ 18 ]. In our study, we also proved that ZNF354C, as a transcriptional factor, could directly bind the promoter of TFPI.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger proteins (ZNF) are a class of transcription factors with multiple functions [ 16 ]. Specifically, ZNF354C has been found to have a critical role in bone and tumors [ 17 , 18 ]. To further investigate the possible mechanisms of TFPI in LIRI, we applied bioinformatic analysis to predict the potential proteins that can bind to the TFPI promoter and concluded that ZNF354C may have a direct targeting regulatory role with the TFPI promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 632 CDS, ZNF354C was upregulated (log2FC 1.9) in stage 1 only, whereas TCN1 (log2FC 2.0) and MAGI3 (log2FC 1.4) were upregulated in stage 2 blood only (Fig 4B) . Overexpression of ZNF354C has a crucial role in inhibition of endothelial cell sprouting (31). TCN1 expression in blood is negatively associated with poor verbal memory performance (32).…”
Section: Resultsmentioning
confidence: 99%
“…in stage 2 blood only (Fig 4B). Overexpression of ZNF354C has a crucial role in inhibition of endothelial cell sprouting(31). TCN1 expression in blood is negatively associated with poor verbal memory performance(32).…”
mentioning
confidence: 99%
“…ZNF354C acts as an inhibitory transcription factor in its KRAB domain dependent on speci c amino acids. Overexpression of ZNF354C leads to transcriptional inhibition of many genes (Oo et al 2020). The expression among the three cell lines was not the same in the regions of-310 ~ 560bp, -1203~-1369bp, and-1369~-1626bp.…”
Section: Discussionmentioning
confidence: 99%